A student's introduction to English grammar - Huddleston, Rodney D.; Pullum, Geoffrey K.; Reynolds, Brett, 1969- ([Cambridge, United Kingdom] ; [New York, N.Y.] : Cambridge University Press, 2021)
"In a sense, you already know English grammar. You must, in some unconscious way, if you're reading this. But being able to do something is different from understanding exactly what's being done. Knowing how to walk isn't the same as appreciating the anatomy of the human leg. The study of grammar involves developing an explicit account of how sentences are put together"--
Introduction. The English language -- Describing and advising -- The structure of sentences -- Investigation and disconfirmation -- Exercises on chapter 1 -- Overview of the book. Word forms and lexemes -- Phrases and clauses -- Verbs and verb phrases -- Complements in the clause -- Nouns and noun phrases -- Adjectives and adverbs -- Prepositions -- Adjuncts -- Negation -- Clause type -- Subordinate clauses -- Relative constructions -- Comparative and superlative constructions -- Non-finite clauses -- Coordination -- Information packaging -- Appendix: Notational conventions -- Exercises on chapter 2 -- Verbs and verb phrases. Verb inflection -- Auxiliary verbs -- Perfective and imperfective interpretations -- Primary tense : the present and preterite -- Secondary tense : the perfect -- Progressive aspect -- Modality and the modal system -- Exercises on chapter 3 -- Complements in clauses. Introduction -- The subject -- The object -- Predicative complements -- Overview of complementation in VPs -- Exercises on chapter 4 -- Nouns and determinatives. Introduction -- Number and countability -- Determiners and determinatives -- Complements in NP structure -- Internal modifiers in nominals -- External modifiers -- The fused-head construction -- Pronouns -- Genitive case -- Exercises on chapter 5 -- Adjectives and adverbs. Adjectives -- Adverbs -- Exercises on chapter 6 -- Prepositions and particles. The traditional category of prepositions -- Extending the preposition category -- Further category contrasts -- Grammaticized uses of prepositions -- Preposition stranding -- The structure of PPs -- PP complements in clause structure -- Prepositional idioms and fossilization -- Exercises on chapter 7 -- Adjuncts : modifiers and supplements. Introduction -- Manner, means, and instrument -- Act-related adjuncts -- Space and time -- Degree -- Purpose, reason, and result -- Concessives -- Conditionals -- Four other clause-modifying adjuncts -- Connective adjuncts -- Supplements -- Exercises on chapter -- Negation. Negative and positive clauses -- Subclausal negation -- Clausal negation -- Non-affirmative items -- Scope of negation -- Exercises on chapter 9 -- Clause type. Speech acts and types of clause -- Interrogatives and questions -- Exclamatives -- Imperatives and directives -- Performative use of speech act verbs -- Minor clause types -- Exercises on chapter 10 -- Subordinate clauses. Subordination -- Clause type in content clauses -- Declarative content clauses -- Interrogative content clauses -- Exclamative content clauses -- Exercises on chapter 11 -- Relative constructions. Relative clauses as modifiers in nominals -- Integrated vs supplementary relatives -- Integrated and supplementary relative words -- Fused relatives -- A relative clause that doesn't modify a noun -- Exercises on chapter 12 -- Comparatives and superlatives. Grade inflection -- More and most -- Less and least -- Comparison of equality -- Non-scalar comparison -- Comparative clauses -- Exercises on chapter 13 -- Non-finite clauses. Finite and non-finite clauses -- The form and meaning of non-finite clauses -- The functions of non-finite clauses -- Transparent verbs and raised subjects -- Verbless clauses -- Exercises on chapter 14 -- Coordinations. The structure of coordinations -- Distinctive syntactic properties of coordination -- The order of coordinated constituents -- The marking of coordination -- Layered coordination -- Main-clause and lower-level coordination -- Joint vs distributive coordination -- Non-basic coordination -- Exercises on chapter 15 -- Information structure. Introduction -- Passive clauses -- Extraposition -- Existential clauses -- The it-cleft construction -- Pseudo-clefts -- Dislocation: He's clever, your dad -- Preposing and postposing -- Reduction -- Exercises on Chapter 16.
Includes index.
Keywords: English language -- Grammar; LANGUAGE ARTS & DISCIPLINES / General